Assessment of Barriers to the Utilization and Acceptance of Low Vision Devices: 10.36351/pjo.v39i1.1518 - Afzaal, Wardah; Irum Riaz; Jan, Ubaidullah; Noor, Shahid; Sohail, Ahmed (Pakistan Journal of Ophthalmology, 2022)
Purpose: To assess barriers to the utilization and acceptance of Low vision devices (LVDs). Study Design: Cross sectional study. Place and Duration of Study: LRBT Hospital, Lahore from February 2022 to June 2022. Methods: The study included 117 patients who noticed an improvement in the LVDs trial but were still reluctant to use LVDs. Patients with best-corrected visual acuity (BCVA) of < 1/60 or a remaining visual field of less than 5˚around central fixation were not included. Patients with lower cognitive levels or psychiatric impairments were also excluded from participating. Self-structured questionnaire was used. Data on age, gender, occupation, diagnosis, preferred LVDs, patient’s impression of visual loss, and the main cause of LVDs rejection were analyzed. The Chi-square test was used to determine association. A value of (P < 0.05) was considered significant. Results: The highest non-acceptance rate (45.2%) was seen in patients > 60 years of age. Leading causes for non-acceptance of LVDs were social stigma in patients aged < 40 years (29.7%), fear of losing a job in patients aged 41-60 years (26.1%), and low necessity in patients aged > 60 years (30%).The rate of non-acceptance was highest for retinitis pigmentosa (71.4%) and lowest for diabetic retinopathy (12.5%). Handheld magnifiers had the lowest non-acceptance rate of all the devices (45%).Non-acceptance rates were higher for telescopes and non-optical devices (77.8% and 73.3% respectively). Conclusion: The reasons for limited LVDs utilization go beyond affordability or availability. Understanding these barriers can facilitate in devising content for the patient, healthcare professionals, and general public awareness campaigns.